2018
DOI: 10.1111/ijmr.12175
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Performance Measurement Theory by Focusing on Subjects: Lessons from the Measurement of Social Value

Abstract: Performance measurement and management (PMM) researchers have recently called for a closer inspection of social controls – the cultural and behavioural aspects of PMM inside organizations – as a complement to longstanding inquiries into technical controls – the rational and structural processes that enable measurement. The authors address this call by first reviewing the principal findings obtained in the field of social value measurement (SVM), which focuses on the measurement of how and to what extent indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 105 publications
(241 reference statements)
1
40
0
2
Order By: Relevance
“…Previous researchers have shown that if companies aim to create and sustain a competitive advantage through collaboration, their organizational routines should be understood (Beer and Micheli, 2018); otherwise, the objectives will not be achieved, and the collaboration will fail (Verdecho, Alfaro, and Rodriguez-Rodriguez 2009; Pekkola and Ukko 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous researchers have shown that if companies aim to create and sustain a competitive advantage through collaboration, their organizational routines should be understood (Beer and Micheli, 2018); otherwise, the objectives will not be achieved, and the collaboration will fail (Verdecho, Alfaro, and Rodriguez-Rodriguez 2009; Pekkola and Ukko 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although many frameworks for measuring the performance of the supply chain have been developed, little is known about the mechanisms that initiate and enhance social interactions in performance measurement (Smith and Bititci 2017;Beer and Micheli 2018). Successful supply chain relationships require firms work independently and in collaboration with other supply chain actors, by encouraging, for example, exchanging information in a trusting manner, joint sense making and integrating knowledge (Poppo, Zhou, and Ryu 2008;Cheung, Myers, and Mentzer 2010;Papakiriakopoulos and Pramatari 2010;Liang 2015;Nollet, Beaulieu, and Fabbe-Costes 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations